Pension fund capitalism: a causal analysis - Clark, G (Blackwell Publishing, 1998)
Since 1980, UK individual pension and retirement assets have increased about twelvefold to around £1.5 trillion. Over the same period, US household retirement assets have increased about tenfold to more than US$7 trillion. High rates of asset growth have also been observed for Australia and Canada. Notwithstanding their current high standards of living, countries in much of continental Europe have not shared in these extraordinary rates of growth of pension assets. In fact, many analysts believe that their long-term prosperity is threatened (relatively speaking) by inefficient, institutionally cumbersome finance sectors. While saving now for retirement has significant advantages for beneficiaries, less recognized is the fact that the growth of pension assets in the Anglo-American economies has profoundly changed the financial structure of these countries. In this paper I explain how and why pension assets have grown so large in the Anglo-American countries, beginning with a historical accounts which helps to identify the reasons why German and continental European countries (excluding The Netherlands and Switzerland) have not shared the same rates of growth in pension assets. In doing so, the paper develops a causal model which discriminates between various causes of Anglo-American pension fund capitalism: structural determinants (institutional framework), second-order determinants (postwar conditions), and third-order determinants (the flow of contributions). The identified causal logic integrates structure with historical and geographical contingency. Implications are also drawn regarding the significance of Anglo-American pension funds for global capitalism.